2016
DOI: 10.1080/00480169.2016.1244021
|View full text |Cite
|
Sign up to set email alerts
|

Periparturient characteristics of mares and their foals on a New Zealand Thoroughbred stud farm

Abstract: Accurate measures for periparturient behaviour can be important in the management of mares and newborn foals. Clinically relevant differences appear to exist between mares and foals in New Zealand and those in the Northern Hemisphere for some key parameters, likely as a result of differences in management and environment. The results of this study suggest that mares should be considered to have retained their membranes if not passed within 4 hours of parturition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 14 publications
1
6
1
4
Order By: Relevance
“…This result is in agreement with the literature, in which malposture of the extremities accounted for 41% of equine dystocia [ 6 ]. Differently from what is reported in Thoroughbred foaling [ 46 ], feto-maternal disproportion due to fetal oversize was not observed. In fact, the median foal weight was within normal range for foals of average size.…”
Section: Discussioncontrasting
confidence: 99%
“…This result is in agreement with the literature, in which malposture of the extremities accounted for 41% of equine dystocia [ 6 ]. Differently from what is reported in Thoroughbred foaling [ 46 ], feto-maternal disproportion due to fetal oversize was not observed. In fact, the median foal weight was within normal range for foals of average size.…”
Section: Discussioncontrasting
confidence: 99%
“…As recently reported [33], normal gestation length in the THB mares included in this study ranged between 330 and 396 days, with a mean of 352 days. All THB included in the present study were housed in the Waikato region, New Zealand, where the hours of daylight ranged from 11.20 to [12] is that the equine uterus needs to be in some way primed by a first pregnancy before it can achieve its full potential in terms of facilitating fetal growth.…”
Section: Discussionsupporting
confidence: 50%
“…Four to six hours post-partum have also been proposed as still being within the physiological range ( 7 , 22 ). Personal communications suggest that some specialist theriogeniologists already consider membranes retained if not expulsed by 1 h post-partum, which is supported by the findings of a recent study that reported fetal membrane release within 1 h in two-thirds of mares ( 5 ).…”
Section: Discussionmentioning
confidence: 74%
“…The duration of time before the membranes are considered to be retained varies widely from 30 min to up to 24 h ( 2 – 4 ). A recent study found that 95% of Thoroughbred mares expelled their membranes within 4 h, whereby more than two-thirds of the mares had already expelled them after 1 h ( 5 ).…”
Section: Introductionmentioning
confidence: 99%